2004
DOI: 10.1590/s0001-37652004000400009
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctions in hematopoietic stroma control proliferation and differentiation of blood cell precursors

Abstract: We examined gap junction communication in an in vitro model of hematopoiesis, using the murine bone marrow stroma cell line S-17, and primary cultures of murine marrow-derived blood cell precursors. S-17 cells express several connexins, the major one being connexin 43. Connexin expression and formation of functional gap junctions is modulated by stroma cell density. Transfection of S-17 cells with a vector containing connexin 43 sense or anti-sense sequences increased or decreased, respectively, connexin 43 sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…S5J). Such intercellular GAP junction formation among stromal cells is known to positively regulate HSCs . These data suggest that the increased intercellular transfer of molecular cargo by the M2‐AKT cells may be related to deregulated formation of gap‐junctions.…”
Section: Resultsmentioning
confidence: 80%
“…S5J). Such intercellular GAP junction formation among stromal cells is known to positively regulate HSCs . These data suggest that the increased intercellular transfer of molecular cargo by the M2‐AKT cells may be related to deregulated formation of gap‐junctions.…”
Section: Resultsmentioning
confidence: 80%
“…Two other groups also reported no detectable Cx43 expression in rat microglia, including activated‐like cells, when cocultured with astrocytes (Rouach et al, 2002; Faustmann et al, 2003). Cx43 expression has been found in numerous other hematopoietically derived macrophages and other immune system cells (Rosendaal et al, 1994; Eugenin et al, 2001, 2003; Oveido‐Orta et al, 2004; Bodi et al, 2004) but apparently was absent from F4/80‐positive macrophages in bone marrow (Rosendaal et al, 1994). Additional studies will be necessary to resolve Cx expression patterns in microglia fully.…”
Section: Discussionmentioning
confidence: 99%
“…The diffuse red shown in stromal cells for connexin-43 served as our internal positive control because these cells express connexin. 30,31 Trypan blue exclusion indicated no evidence of BCC death. Together, these findings demonstrate gap junction formation after the BCCs have contacted BM stroma.…”
Section: Formation Of Gap Junctions Between Bccs and Bm Stromamentioning
confidence: 99%
“…22 Furthermore, BM stromal cells as well as low metastatic BCCs can form gap junctions. [29][30][31] In vitro studies with cocultures of BM stroma and BCCs have shown normal hematopoietic functions. 22 We now ask whether BM stroma and BCCs form gap junctions.…”
Section: Formation Of Gap Junctions Between Bccs and Bm Stromamentioning
confidence: 99%